MISCONCEPTIONS ON THE CONCEPT OF PHOTOSYTHESIS AND PLANT RESPIRATION FOR CLASS VIII AT SMP NEGERI 27 MEDAN IN SCIENCE LEARNING - G A Manurung; L A Simanjuntak; R A Sihombing (ISER (Indonesian Science Education Research), 2021)
This research aims to find out the misconceptions that occured in the concept of photosynthesis andplant respiration for Class VIII at SMP Negeri 27 Medan In Science Learning. The research methodused by the writer in this research was descriptive qualitative method. The methodology itself was aprocess, principles, and procedures that use to approach problems and seek answers. The datacollection technique was carried out through the technique of giving a modified google formquestionnaire from a Denise journal questionnaire (2018) to several junior high school teachers inthe city of Medan. Interviews were conducted to find out more in-depth things related to themisconceptions that occur in students on the concepts of photosynthesis and respiration. The resultsof the analysis of the misconception questionnaire and interview data by teacher and students inClass VIII at SMP Negeri 27 Medan were presented. Based on the results of the research anddiscussion, it can be concluded that the misconceptions of class VIII students at SMP Negeri 27Medan fall into the “misconception” category with the criteria of “low” on the material ofPhotosynthesis and Plant Respiration.